Is biparental defence driven by territory protection, offspring protection or both?. (June 2021) - Zimmermann, Holger; Bose, Aneesh P.H.; Ziegelbecker, Angelika; Richter, Florian; Bračun, Sandra; Eisner, Helgit; Katongo, Cyprian; Banda, Taylor; Makasa, Lawrence; Henshaw, Jonathan M.; Fritzsche, Karoline; Sefc, Kristina M.
Abstract : In many animal systems, the defence of a territory or nest coincides with the defence of offspring, and it is often unclear whether the defence behaviour exists for the purpose of offspring protection, territory protection or a combination of both. In species with biparental care, the drivers of defence behaviours in males may differ from those in females, particularly if there are sex-specific fitness benefits from the current brood or territory. In this study, we present field experiments aimed at elucidating sex differences in the drivers behind nest defence in a fish species ( Variabilichromis moorii, Cichlidae) with biparental care. High rates of cuckoldry in this species create asymmetries in brood value between mates, suggesting that increased brood survival may be a weaker driver of male than of female defence effort. We conducted parent and offspring removal experiments and found that following the removal of their mates, single males lost significantly more fry than single females. Some single males lost their territories, while others constricted their space use, suggesting that experimental divorce decreased their success in territory defence. Removal of fry from territories guarded by both parents caused the defence behaviour to become more male biased, that is, males contributed relatively more to defence without any fry present. Our results suggest that, relative to that of females, male defence behaviour is more strongly driven by territory retention than by brood protection. Nevertheless, the presence of males improves parents' abilities to keep territory intruders at bay, and thus probably confers benefits to broods. We conclude that the drivers of defence behaviours differ between the sexes in this species, with defence behaviours aligning well with the traditional definition of parental care for females, but less so for males. Highlights: We experimentally probed the drivers of defence behaviours in a biparental fish. Experimentally divorced males suffered higher brood losses than single females. Male defence probably functions more as protection of territory than brood. Intruders encroach further into territories of single females than paired females. Sex-specific drivers for defence probably reflect value of brood to each parent.